TEMPORAL ANALYSIS OF THE REPORTS TO THE POLICE LINE (155) RELATED TO STREET CRIMES IN THE CITY OF DIYARBAKIR - Donmez, Mustafa (European Scientific Journal, ESJ, 2014)
The prevalence of crime is a major problem in Turkey, and the city of Diyarbakir is among the cities in Turkey where crime rate is very high. Therefore, reporting of crimes to the police is very crucial in finding criminals and reducing crime rate. It is expected that there is a correlation between the time a crime is committed and the time of reporting. The aim of this study is to reveal the temporal distribution of the reports related to some street crimes such as purse-snatching, theft forms in workplaces, and burglary. A descriptive analysis was conducted in order to analyze the temporal distribution of reports of the crimes in 2011 in the city of Diyarbakir. However, it was found that the police take most of the reports on Saturdays. Reporting criminal suspects reaches the peak on Sundays. The least reports on crimes were made between 01.00 a.m. and 04:00 a.m., while most of the report was made between 05:00 and 08:00 in the mornings. The findings were discussed at the end of this article.